2020
DOI: 10.1002/med.21767
|View full text |Cite
|
Sign up to set email alerts
|

Protein corona formed in the gastrointestinal tract and its impacts on oral delivery of nanoparticles

Abstract: The interaction of nanoparticles (NPs) with proteins and the formation of protein corona in the biological fluids are of great interest and significance for drug delivery. In the past decade, the corona formation in the blood and its impacts on the in vitro and in vivo fate of NPs has been well investigated and reviewed. Recently, more and more attention is paid to the nano–protein interactions taking place in the gastrointestinal tract (GIT) between the orally administered NPs and the digestive enzymes. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 88 publications
0
22
0
Order By: Relevance
“…In recently published studies, Zhang et al provided a brief summary of the latest developments on the nano-protein interactions between NPs and enzymes of the digestion and initiated an engaging discussion on the possibility of the use of the digestive enzyme corona for the targeted delivery in the colon. 216 The authors described physicochemical properties that are closely linked to the oral absorption of NPs, which include: size, zeta potential and surface molecules, which are greatly affected by the interaction of nano-enzymes and the formation of the enzyme corona. Moreover, it has been shown that the uptake of NPs by epithelial cells is significantly increased after the formation of the enzyme corona.…”
Section: Pharmacokinetic and Toxicological Studies Of Nanoparticles As A Delivery Systemmentioning
confidence: 99%
“…In recently published studies, Zhang et al provided a brief summary of the latest developments on the nano-protein interactions between NPs and enzymes of the digestion and initiated an engaging discussion on the possibility of the use of the digestive enzyme corona for the targeted delivery in the colon. 216 The authors described physicochemical properties that are closely linked to the oral absorption of NPs, which include: size, zeta potential and surface molecules, which are greatly affected by the interaction of nano-enzymes and the formation of the enzyme corona. Moreover, it has been shown that the uptake of NPs by epithelial cells is significantly increased after the formation of the enzyme corona.…”
Section: Pharmacokinetic and Toxicological Studies Of Nanoparticles As A Delivery Systemmentioning
confidence: 99%
“…The formation of protein corona is affected by many factors, mainly including the physical and chemical properties of nanoparticles and nanoparticles (NPs) exposure concentration. It is found that the traditional oral drug treatment results for inflammatory bowel disease, colon cancer, and other colon diseases are not ideal, but after NPs enzyme corona complex is transported to the colon, after bacteria degrade enzymes, canopy and nanoparticles, its loaded drugs can be released in the colon to achieve targeted treatment of colon diseases [146]. Researchers found that although the targeting of NPs can be promoted by modifying the surface, the results are often disappointing.…”
Section: Discussionmentioning
confidence: 99%
“…Besides various types of biomolecules existent inside or on the surface of EVs, recent studies have shown that EVs, after entering gastrointestinal tract, blood, or even cell culture media, can readily bind proteins and form a protein corona on the surface. [93,94] Protein corona on nano particles can significantly affect their surface charges and overall sizes, affecting biodistribution and theranostic functions. [95] Hence, it would be essential to consider protein corona when EVs were used for in vivo drug delivery applications.…”
Section: Proteinsmentioning
confidence: 99%